A Grassmanniana e a dimensão da variedade de fano de uma hipersuperfície - Allan de Sousa Soares (2011)
The Grassmannian G(k; n) corresponds to the linear k-dimensional subespaces of Pn. Thus, given a variety X Pn of degree d, we de ne the Fano variety Fk(X) as a submanifold of G(k; n) formed by the k-dimensional linear spaces contained in X. In the case where X is hypersurface we will study, from the parameters n, k, d, under what conditions this variety is not empty. In the case that this variety is not empty will determine its dimension. Furthermore, we show that Fano variety of lines of a cubic surface without singular points of X P3 is composed of exactly 27 lines.